2017
DOI: 10.1093/nar/gkx1255
|View full text |Cite
|
Sign up to set email alerts
|

PolyC-binding proteins enhance expression of the CDK2 cell cycle regulatory protein via alternative splicing

Abstract: The PolyC binding proteins (PCBPs) impact alternative splicing of a subset of mammalian genes that are enriched in basic cellular functions. Here, we focus our analysis on PCBP-controlled cassette exon-splicing within the cell cycle control regulator cyclin-dependent kinase-2 (CDK2) transcript. We demonstrate that PCBP binding to a C-rich polypyrimidine tract (PPT) preceding exon 5 of the CDK2 transcript enhances cassette exon inclusion. This splice enhancement is U2AF65-independent and predominantly reflects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 63 publications
(117 reference statements)
1
9
0
Order By: Relevance
“…Phosphorylated CDC6 translocates to the cytoplasm to prevent re-replication of the DNA [57] (Figure 1). Regulation of CDK2 alternative splicing by exclusion of exon 5 represses CDK2 protein expression and thus impacts cell cycle control [58]. The regulation of CDK2 alternative splicing is coordinated by poly(rC) binding protein 1 and 2 (PCBP1/2) as well as the splicing factor PTB.…”
Section: Cdc-like Kinase 1 (Clk1)mentioning
confidence: 99%
“…Phosphorylated CDC6 translocates to the cytoplasm to prevent re-replication of the DNA [57] (Figure 1). Regulation of CDK2 alternative splicing by exclusion of exon 5 represses CDK2 protein expression and thus impacts cell cycle control [58]. The regulation of CDK2 alternative splicing is coordinated by poly(rC) binding protein 1 and 2 (PCBP1/2) as well as the splicing factor PTB.…”
Section: Cdc-like Kinase 1 (Clk1)mentioning
confidence: 99%
“…CDK2 and cyclin E1 have been regarded to be cell cycle regulators in malignant tumors. [30][31][32][33] Moreover, Liu et al found that NF-κB induced cell cycle arrest in laryngeal squamous cell cancer via downregulation of CDK2. 34 Overexpression of p38γ could promote the progression of human colorectal cancer via upregulation of cyclin E1.…”
Section: Dovepressmentioning
confidence: 99%
“…Previously, it has been demonstrated that RNA splicing and cell cycle are interconnected. Adequate splicing of cell cycle genes, such as CDC25 and CDK2, are required for a proper transition between different cell cycle phases 49,50 and disruption of core spliceosome components, such as deletion of SRSF2, leads to G2-phase cell cycle arrest and apoptosis [51][52][53] . It is possible that mutant splicing factors diminish the capacity of the spliceosome, which is critical for normal cell cycle progression, and that mutant cells heavily rely on the remaining wildtype allele for survival.…”
Section: Discussionmentioning
confidence: 99%